2018
DOI: 10.1002/adsc.201800791
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Enantioselective Synthesis of α‐Amino‐δ‐Ketoesters Through Catalytic Umpolung Reaction of α‐Iminoesters with Enones

Abstract: Chiral a-amino-d-keto esters are important precursors of organocatalysts, pharmaceuticals, and biochemically interesting molecules. The organocatalytic asymmetric umpolung reaction of imines has been developed to obtain chiral amines in a highly enantioselective manner. Herein, we report the organocatalytic asymmetric umpolung synthesis of a-amino-d-keto esters in high yield (up to 95% ee, > 20/1 r.r.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…We started the investigation with the model reaction of trifluoromethyl imine 1A and methyl acrylate ( 4a ) by utilizing our previously developed cinchona phase-transfer catalyst C- 1 . However, the substantially decreased electrophilicity of 4a posed considerable challenges . Specifically, we observed that the activated 2-azaallyl anion intermediate 2A preferably underwent the isomerization pathway to side product 6A and only a tiny amount of desired adduct 5Aa was obtained with poor enantioselectivity ( 5Aa / 6A = 10/90, 15% ee of 5Aa , entry 1, Table ).…”
Section: Resultsmentioning
confidence: 94%
“…We started the investigation with the model reaction of trifluoromethyl imine 1A and methyl acrylate ( 4a ) by utilizing our previously developed cinchona phase-transfer catalyst C- 1 . However, the substantially decreased electrophilicity of 4a posed considerable challenges . Specifically, we observed that the activated 2-azaallyl anion intermediate 2A preferably underwent the isomerization pathway to side product 6A and only a tiny amount of desired adduct 5Aa was obtained with poor enantioselectivity ( 5Aa / 6A = 10/90, 15% ee of 5Aa , entry 1, Table ).…”
Section: Resultsmentioning
confidence: 94%
“…All dehydrated solvents were purchased from Wako Pure Chemical Industries, Ltd., and were used without further purification. Catalysts 3 were prepared according to the reported procedure. , …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, this process has been successfully applied to several important chemical transformations, and excellent enantioselectivities have been achieved. In 2018, Xiao and co-workers reported the first catalytic umpolung [3 + 2] cycloaddition reaction of imines with nitroolefins, which provided chiral pyrrolidines in up to 99% ee . We have previously developed an ammonium-salt-catalyzed asymmetric umpolung reaction of α-imino esters with α,β-unsaturated carbonyl compounds to give α-tetrasubstituted unnatural amino acid derivatives in up to 98% ee (Figure a) . Although the several important research areas have been disclosed by umpolung reaction of imines so far, this concept has considerable potential for the development of more complex molecular transformations such as organocascade reactions .…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Han and co‐workers reported the Ir/phase‐transfer cooperatively catalyzed asymmetric umpolung allylation of α‐imino esters, which could provide α‐quaternary amino acid derivatives in high yields with up to 96 % ee . We reported the organocatalytic asymmetric umpolung Michael addition reaction of α‐imino esters with acrolein derivatives, which was catalyzed by a chiral phase‐transfer catalyst we originally developed to form the corresponding amino acids with an alcohol functionality in high yields with up to 98 % ee . We recently developed the first chemo‐ and regioselective catalytic asymmetric umpolung organocascade reaction of α‐imino amides, which provided chiral enamides in high yields with >20:1 selectivity and up to 99 % ee …”
Section: Introductionmentioning
confidence: 99%